Sustainable Development Strategy of Virgin Coconut Oil (VCO) Production in Penglipuran Village Based on SWOT Analysis and Sustainable Development Theory - I Ketut Selamet; A.A Sri Purnami; L. G P. Sri Eka Jayanti (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the role of women farmer groups in developing VCO production, identify internal and external factors affecting business sustainability, and formulate appropriate development strategies based on SWOT analysis and sustainable development theory. The research employed a qualitative case study approach. Data were collected through in-depth interviews, observations, documentation, and discussions with members of the women farmer group and village stakeholders. The findings reveal that the women farmer group has substantial potential to support local economic growth and women’s empowerment. The main strengths include active female labor participation, the tourism potential of Penglipuran Village, and increasing market demand for natural health products. However, several weaknesses remain, such as limited production capacity, simple equipment, low digital marketing capability, and limited financial resources. The Internal Factor Analysis Summary (IFAS) score was 2.82, while the External Factor Analysis Summary (EFAS) score was 2.80, indicating that the business position is in cell V of the Internal-External (IE) Matrix, suggesting a hold-and-maintain strategy. The recommended strategy focuses on improving production capacity, strengthening managerial capability, enhancing digital marketing, diversifying coconut-based products, and increasing institutional collaboration. This research contributes to sustainable rural development by promoting local resource utilization, women’s empowerment, and environmentally friendly economic activities.